Fox on the Run—Cheaper Camera Traps Fail to Detect Fast‐Moving Mesopredators - R. McHenry; L. J. Mitchell; C. Marshall; J. Smart; A. L. deRaad; R. Andersen (Ecology and Evolution, 2025)
ABSTRACT Camera trapping for detecting wildlife is increasingly used as a primary method of non‐invasive wildlife monitoring. Yet understanding among researchers and conservationists on how camera trap make, and model affect detection rates is limited. Published studies often fail to make clear why a given camera trap model was chosen or what specifications or parameters were used to capture target species within a given study area, prohibiting replicability. Here we present a comparison of predator and herbivore detection efficacy using three makes and models of camera trap at differing price ranges, year of release (hereafter vintages) and specifications. We used a passive monitoring survey design at six sites in open field conditions across the Flow Country, Northern Scotland. Detection efficacy varied substantially between grades and vintages of camera traps and depended on species captured. Older models of camera with lower trigger speed and night vision range performed particularly poorly for nocturnal predatory mammal detection. This has implications for how researchers, conservationists, developers and other users approach experimental design and analyses, but also on the conclusions that may be drawn from studies. We caution against using the results of one or more camera trap studies using different makes and models of cameras to inform experimental design or policy interventions.